Integration of battery electric vehicles in a regional hydro–wind–thermal power system. (December 2020) - Li, Bo; Chen, Minyou; Li, Qiang; Cheng, Tingli; Ma, Ziming; Zhang, Shujun; Qian, Xiao
Abstract: The deployment of renewable electricity and electric vehicles (EVs) provides a synergistic opportunity to accelerate both the decarbonization of the power system and the transportation sectors. This study investigates the consequences of integrating electric vehicles (EVs) in the Chongqing thermal–hydro–wind power system by using the unit commitment model. We focus on how EVs integration strategies (smart charging and unmanaged charging) impact the power system, in terms of operating costs, CO2 emissions, and curtailment of renewables of the power system. We choose the year 2030 as a study year, and the future electricity demand, installed capacity, and EVs population in Chongqing are projected in this study. Monte Carlo simulations are applied to model EV's charging behaviors based on the statistics of private vehicles. The results show that EVs could reduce CO2 emissions from the power system if coupled with active integration strategies, whereas a passive integration strategy is likely to increase CO2 emissions. Furthermore, CO2 emissions of EVs when running the power system can be 74.2 % lower than the emissions from gasoline-driven vehicles (220 g/km). Economically, the results show that a smart charging strategy saves 201 per EV more annually than does a case where the charging is unmanaged.